2015
DOI: 10.1371/journal.pone.0145093
|View full text |Cite
|
Sign up to set email alerts
|

Morin, a Bioflavonoid Suppresses Monosodium Urate Crystal-Induced Inflammatory Immune Response in RAW 264.7 Macrophages through the Inhibition of Inflammatory Mediators, Intracellular ROS Levels and NF-κB Activation

Abstract: Our previous studies had reported that morin, a bioflavanoid exhibited potent anti-inflammatory effect against adjuvant-induced arthritic rats. In this current study, we investigated the anti-inflammatory mechanism of morin against monosodium urate crystal (MSU)-induced inflammation in RAW 264.7 macrophage cells, an in vitro model for acute gouty arthritis. For comparison purpose, colchicine was used as a reference drug. We have observed that morin (100–300 μM) treatment significantly suppressed the levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 39 publications
2
45
0
Order By: Relevance
“…Besides to its antioxidant property, morin administration also proved to show anti-inflammatory properties in several animal models [41][42][43]. Emerging evidence have shown that antiinflammatory properties of morin are mediated through attenuation of ROS mediate NF-jB activation and amelioration of mitochondrial dysfunction [21,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Besides to its antioxidant property, morin administration also proved to show anti-inflammatory properties in several animal models [41][42][43]. Emerging evidence have shown that antiinflammatory properties of morin are mediated through attenuation of ROS mediate NF-jB activation and amelioration of mitochondrial dysfunction [21,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB can form a tripolymer by combining with inhibitor of NF-κB (IkB). When IkB degrades and is lost, a dipolymer with transcriptional activity is formed (9). The activated dipolymer has the following functions in renal interstitial fibrosis (8): Firstly, it is associated with fibroblast growth factors generated by fibroblasts and intrinsic renal cells.…”
Section: Discussionmentioning
confidence: 99%
“…As an important factor for the control of genetic transcription, nuclear factor (NF) -κB may be activated by the stimulation of cytokines, protein kinase, viruses and oxidizing agents (8). The activated NF-κB can induce the expressions of cytokines, growth factors and chemotactic factors, and be involved in pathological processes, including inflammatory responses, fibrosis, tumor development and atherosclerosis (9). Activated NF-κB can promote the transcription of monocyte chemoattractant protein-1, the excessive expression of which reduces the infiltration of macrophages and interstitial fibrosis (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Gout is characterized by the deposition of MSU crystals in joints, which is associated with the rise of serum urate content, leading to excruciating pain and inflammatory events [50,51]. MSU crystals deposits or tophi further induce chronic inflammatory responses that may lead to joint damage, often referred to as gouty arthritis or chronic gout [52].…”
Section: A C C E P T E Dmentioning
confidence: 99%